2015
DOI: 10.1111/bju.13147
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic arterial embolization for the treatment of lower urinary tract symptoms caused by benign prostatic hyperplasia: a comparative study of medium‐ and large‐volume prostates

Abstract: ObjectivesTo compare the outcomes of prostatic arterial embolization (PAE) in treating large (>80 mL) in comparison with medium-sized prostate glands (50-80 mL) to determine whether size affects the outcome of PAE. Patients and MethodsA total of 115 patients (mean age 71.5 years) diagnosed with lower urinary tract symptoms (LUTS) attributable to benign prostatic hyperplasia (BPH) refractory to medical treatment underwent PAE. Group A (n = 64) included patients with a mean prostate volume of 129 mL; group B (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 24 publications
(34 reference statements)
3
49
1
5
Order By: Relevance
“…A minimum of 10 patients in the sample size was applied as inclusion criteria. In total, 7 trials on PAE for LUTS were identified having fully published their findings [3,4,5,6,7,8,9].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A minimum of 10 patients in the sample size was applied as inclusion criteria. In total, 7 trials on PAE for LUTS were identified having fully published their findings [3,4,5,6,7,8,9].…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, Wang et al published findings comparing outcomes of PAE in the treatment of large sized prostates (>80ml) versus medium sized prostates (50-80ml) [9]. Their results revealed a significantly greater improvement in IPSS, QoL, Qmax, PVR and PV in the group with large sized prostates.…”
Section: The History Of Prostatic Arterial Embolizationmentioning
confidence: 99%
See 1 more Smart Citation
“…), büyük mesane taşı, kronik böbrek yetmezliği, aktif üriner enfeksiyon ve düzeltilemeyen koagülo-pati PAE için kontraendikedir [32,33]. Transüretral prostat rezeksiyonunun (TURP) aksine PAE'da prostat hacmi için bir üst sınır olmayıp literatürdeki kısa ve orta dönem çalışmalar bü-yük hacimli prostatların (>80cm 3 ) PAE sonrası ek komplikasyon riski oluşturmadığını göster-miştir [29,[34][35][36].…”
Section: Pae Için Hasta Seçimi Ve Değerlendirmeunclassified
“…Wang et al 59 , na tentativa de comparar o resultado da EAP em próstatas de diferentes dimensões, utilizaram também partículas não esféricas de PVA com diâmetro de 47-90 µm, após cateterismo superseletivo distal das artérias prostáticas, obtendo estase parcial. Depois realizavam oclusão do respectivo vaso proximalmente com partículas pouco maiores (90 a 180 µm) até estase completa, com sucesso técnico e clínico.…”
Section: Escolha Do Agente Embolizanteunclassified